2021
DOI: 10.1021/acscentsci.1c00389
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Catalysis Framework to Dissect Proteasomal Degradation Paradigms

Abstract: Diverging from traditional target inhibition, proteasomal protein degradation approaches have emerged as novel therapeutic modalities that embody distinct pharmacological profiles and can access previously undrugged targets. Small molecule degraders have the potential to catalytically destroy target proteins at substoichiometric concentrations, thus lowering administered doses and extending pharmacological effects. With this mechanistic premise, research efforts have advanced the development of small molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 114 publications
1
20
1
Order By: Relevance
“…of cooperativity values, 25 and that over-stabilization of the ternary complex can negatively impact degradation. 7,25,26 Similarly, our model suggests that the optimal range of cooperativity depends on the ubiquitination rate (Fig. 8a).…”
Section: The Effect Of Cooperativity On Degradationsupporting
confidence: 65%
See 2 more Smart Citations
“…of cooperativity values, 25 and that over-stabilization of the ternary complex can negatively impact degradation. 7,25,26 Similarly, our model suggests that the optimal range of cooperativity depends on the ubiquitination rate (Fig. 8a).…”
Section: The Effect Of Cooperativity On Degradationsupporting
confidence: 65%
“…Our results explain the experimental observation that efficient HBF degraders may have a wide range of cooperativity values, 25 and that over-stabilization of the ternary complex can negatively impact degradation. 7,25,26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is the ability of the ligase to form degradation-competent ternary complexes between the ligase and POI. Ternary complex formation is a necessary step in the action of a PROTAC molecule, but the degree of ternary complex formation may differ from substrate to substrate 127 ; that is, a ternary complex that forms too efficiently and remains tightly bound will not lead to efficient degradation. Cooperativity of the ternary complex, which is a measure of ternary complex formation in a heterobifunctional system, may be positive or negative between a ligase and a target enabled by a PROTAC molecule 128 and has been shown to lead to degradation in both cases.…”
Section: Outlook For the Next 20 Years Of Tpdmentioning
confidence: 99%
“…14,15 The formation of the POI-degrader-ligase ternary complex is central to the targeted protein degradation (TPD) process, but how the formation of the ternary structure impacts protein degradation is still poorly understood, especially given the dynamic nature of the complex. [16][17][18][19] X-ray crystallography of the ternary complex 20 provides a high resolution structure of a single conformational state, but a growing body of evidence suggests that the dynamic nature of the ternary structure may not be accurately represented by this lowest energy crystallization snapshot. For instance, a study of several heterobifunctional degraders found that different degraders displayed different degrees of efficiency, although the corresponding ternary complex structures are nearly identical, thus raising questions about the static structural representations of the ternary complex and degradation efficiency.…”
Section: Introductionmentioning
confidence: 99%